COMPARISON OF ALVARADO, RIPASA, AND AIR SCORING SYSTEM IN DIAGNOSIS OF ACUTE APPENDICITIS - KHAN, SB; ZULFIKAR, I; MAQBOOL, N; SHEIKH, K; RIMSHA, S; SHAKEEL, B (Biological and Clinical Sciences Research Journal, 2024)
Accurate and timely diagnosis of acute appendicitis is critical in preventing complications and guiding surgical intervention. The Alvarado, RIPASA, and AIR scoring systems are commonly used diagnostic tools, each with varying performance metrics in different clinical settings. Objective: This study aimed to compare the diagnostic performance and overall accuracy of the Alvarado, RIPASA, and AIR scoring systems for diagnosing acute appendicitis. Methods: This observational study was conducted at Civil Hospital Karachi from December 2023 to May 2024, following ethical approval from the institutional review board. A total of 200 patients aged over 18 years presenting with clinical symptoms suggestive of acute appendicitis were included in the study through non-probability consecutive sampling. Each patient’s data was analyzed using the Alvarado, RIPASA, and AIR scoring systems to evaluate their diagnostic accuracy, sensitivity, specificity, and area under the curve (AUC). Results: The Alvarado score demonstrated a sensitivity of 88.44%, a specificity of 37.04%, and an overall accuracy of 81.50%, with an AUC of 0.667 (p=0.002). The RIPASA score showed a sensitivity of 81.18%, a specificity of 53.33%, and an accuracy of 77.00%, with an AUC of 0.699 (p=0.001). The AIR score displayed a sensitivity of 81.00%, a specificity of 60.00%, and an accuracy of 82.00%, with an AUC of 0.700 (p<0.001). Conclusion: The Alvarado, RIPASA, and AIR scores each demonstrate diagnostic value in identifying acute appendicitis, though their sensitivity and specificity may vary based on the population and clinical setting. Clinicians should consider these variations when selecting a scoring system to optimize diagnostic accuracy for acute appendicitis.